Sweet flow: exploring the flowability, caking, morphology, and solubility of date sugars as promising sugar substitutes - Mohd Baroyi, Syahrul Anis Hazwani; Rosland Abel, Stashia Eleaness; Al-Awaadh, Alhussein M.; Fikry, Mohammad; Abdul Karim Shah, Nor Nadiah; Mohd Salleh, Faiqa Shazeaa; Garg, Vivek; Deng, Tong; Yusof, Yus Aniza (Elsevier B.V., 2024)
This study investigates the impact of sugar content on the physicochemical properties of oven-dried dates powder from four distinct cultivars—Ajwa, Safawi, Sukkary, and Medjool. The drying process reduced moisture content by approximately 55% (Ajwa), 58% (Safawi), 76% (Sukkary), and 60% (Medjool). Quantification of sugars using High Performance Liquid Chromatography equipped with refractive index detector (HPLC-RI) revealed varying sugar compositions, with Ajwa, Safawi, and Sukkary containing a mix of fructose, glucose, sucrose, maltose, and lactose, while Medjool lacked lactose. Sukkary date powder exhibited superior flowability properties due to lower sugar and moisture content, meeting industry standards, although it displayed a higher tendency to cake compared to white and coconut sugars. Other physicochemical characterisation (pH, colour properties L*(lightness), a*(redness/greenness), b* (blueness/yellowness) values, hygroscopicity, solubility, morphology and chemical structure of all date sugar were also explored in comparison with commercial sugars (white sugar and, brown sugar and coconut sugar) as controls. Notably, Sukkary date powder emerged as a promising cultivar for production, offering reduced clumpiness and stickiness in comparison to Ajwa, Safawi, and Medjool date powders. These findings provide valuable insights for food manufacturers, formulators, and researchers interested in using Sukkary date powder in various foods. The potential use of Sukkary as a sugar substitute or carbohydrate source, suitable for both normal and diabetic individuals, underscores its versatility and highlights avenues for innovation in the food industry especially in confectionary, bakeries, beverages, snack foods or other natural, health-oriented food industries.